Effectiveness of warm blood reperfusion in reducing the incidence of reperfusion injury in cardiac surgery using the aortic cross clamp procedure: A systematic review - Ibnu Sofa; Tuti Herawati; Sri Yona; Muhammad Adam (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The management of cardiac surgery is not devoid of complications, which can result in disability or even mortality. Various interventions are implemented to mitigate the complications associated with cardiac surgery. Warm reperfusion is one of the easy, efficient and harmless intervention options for patients. Purpose: To determine the effectiveness of warm blood reperfusion in reducing the incidence of reperfusion injury in cardiac surgery using the aortic cross clamp procedure. Method: A literature search based on several online databases such as ProQuest, PubMed, Sage Journal, Scopus, SpringerLink, Oxford and Frontiers published from 2018-2024. Results: The results of the study indicate that there are several interventions aimed at reducing the incidence of reperfusion injury. Several interventions can be carried out including: giving warm reperfusion, medication and choosing the type of cardioplegia. Reperfusion injury is measured by several variables such as increased cardiac troponin, arrhythmia, inotropic use and length of stay in the intensive care unit. Conclusion: Warm reperfusion was more effective and efficient compared to several other interventions such as medication and cardioplegia selection.